Effect of Selected Fall-proof Exercises on Fear of Falling and Quality of Life in the Elderly - Hosein Khazanin; Hasan Daneshmandi; Hosein Fakoor Rashid (Sālmand, 2022)
Objectives: Fear of falling in the elderly can be a disabling disease that causes negative outcomes including reduced daily productivity, reduced physical activities, and lower quality of life. The present study evaluates effects of an 8-week training protocol with selected Fallproof exercises on fear of falling and quality of life in the elderly. Methods & Materials: This is a quasi-experimental study that initiated in 2019. Population of the study includes 53 elderly from nursing homes in Rasht, from among which 24 individuals aged 60-74 were selected using convenience sampling based on inclusion criteria. The subjects were randomly assigned to experimental (n=12; 66.41±4.41 and control n=12; 66.16±2.40) groups. Fallproof exercises include a range of multisensory exercises (visual, vestibular, and somatosensory), center of gravity control, postural strategies, and power training including toe and heel walking, knee flexion and extension, adduction and abduction. Training intensity was increased based on overload principle and individual differences in an 8-week training protocol, three times a week for 60 minutes. Paired t-test and covariance analysis were used for intra-group and inter-group comparisons, respectively. Data analysis was performed using SPSS at significance level of P<0.05. Results: Our results indicate that fear of falling P<0.001 and quality of life P<0.01 improved significantly in the experimental group while showing no differences in the control group. Conclusion: It is concluded that Fallproof exercises significantly improve quality of life and reduce fear of falling in the elderly. This is observed in improvements in the experimental group. Considering multidimensional effects of Fallproof exercises and multifactor nature of fear of falling, these training protocols can be applied in rehabilitation programs in care centers for the elderly.